Max Pinckers - Theys, Hans 1963- (Hannibal Books, 2021)
This trilingual book marks the culmination of ten years of collaboration between the photographer Max Pinckers and the writer Hans Theys, who was given permission to use a personal selection from all of Pinckers' photographs to create a classic photo book without having to take into account their original context. The publication also contains an essay in which Theys discusses Pinckers' oeuvre based on thoughts by Susan Sontag. Max Pinckers (b. 1988) is a Belgian artist/photographer. In his work he explores the critical, technological and ideological structures which underpin the creation and consumption of documentary images. For Pinckers, creating a documentary is a speculative process in which reality and truth can be used as multiple and mouldable concepts. He has received several international prizes, including the Prix Levallois, the Edward Steichen Award Luxembourg and the Leica Oskar Barnack Award. Exhibition: Photo Museum, Antwerp, Belgium (26.11.2021 - 13.03.2022).